2017
DOI: 10.1016/j.resuscitation.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairments and subjective cognitive complaints after survival of cardiac arrest: A prospective longitudinal cohort study

Abstract: Cognitive impairments are common in cardiac arrest survivors with executive functioning being mostly affected. Most recovery is seen in the first three months after cardiac arrest. After one year, a substantial number of patients remain impaired, especially in executive functioning. Because of absence of associations between impairments and complaints, cognitive testing using a sensitive test battery is important and should be part of routine follow-up after a cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 37 publications
6
70
1
8
Order By: Relevance
“…Our results appear consistent with previous studies with larger sample sizes, both on global functional scales and specific functional and cognitive dimensions (6,8,12,13,15,32), suggesting that these may be generalizable. Furthermore, we report a rigorous cognitive evaluation, unveiling the importance of processing speed and language impairment in CA survivors, in addition to the classically demonstrated impairments in memory and executive functions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results appear consistent with previous studies with larger sample sizes, both on global functional scales and specific functional and cognitive dimensions (6,8,12,13,15,32), suggesting that these may be generalizable. Furthermore, we report a rigorous cognitive evaluation, unveiling the importance of processing speed and language impairment in CA survivors, in addition to the classically demonstrated impairments in memory and executive functions.…”
Section: Discussionsupporting
confidence: 92%
“…Detailed neuropsychological evaluation detected substantial cognitive impairment in 26% of survivors, higher than the 13% at 3 months or 11% at one year reported in (15) (potentially explained by the higher number of tests considered in our study, 13 vs. 6), but lower than the 50% of patients showing mild cognitive impairment reported in (6). In particular, we revealed that impairment in processing speed (21%) and language (21%) were as frequent as the classical impairments in long-term verbal memory (19%) or executive functions (19% for initiation, 17% for inhibition) (6,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greatest recovery of cognitive function is usually seen in the first 3 months post-arrest, but evidence from several small studies indicates continued improvement in some functions during at least the first year [17,18]. There is a lack of follow-up with neuropsychological instruments examining several cognitive domains.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of follow-up with neuropsychological instruments examining several cognitive domains. Earlier studies on cognition after OHCA have either included a smaller number of participants (less than 50), or investigated more patients (100-300) with elementary cognitive assessments or fewer cognitive domains [10,17,19].…”
Section: Introductionmentioning
confidence: 99%